O21 Use of a virtual reality device for adult life support training; prototype testing and an exploration of users' views and experience. (November 2018) - Bench, Suzanne; Winter, Mr Colin; Francis, Gary
Abstract : Introduction: There are approximately 60 000 cases of adult cardiac arrest in the United Kingdom every year. 1 Immediate initiation of cardiopulmonary resuscitation significantly increases the chances of survival and after calling for help, effectively performing chest compressions is the next most important intervention. 1 2 Virtual reality (VR) devices allow the integration of features of real patients into training in a way that can facilitate interaction and feedback; however, the impact this has on performance and its overall value for teaching basic life support remains under explored. 3 4 Methods: This mixed methods study aimed to undertake initial testing of a VR BLS prototype and to explore the views and experiences of the users. We recruited 23 adult staff members working within London, South Bank University in England, 10 of whom declared previous resuscitation training. Each participant completed a pre and post experience questionnaire and took part in a focus group discussion exploring their views and experiences. Results: Most participants were interested in and had an agreeable VR experience. There was a broad consensus for the use of the VR prototype in basic life support training, although less convincing evidence to support it fully replacing conventional face-to-face training. Some people did not enjoy the experience and felt that the application lacked adequate instruction and feedback. Despite this, confidence and competence did improve for many, particularly the technical skill of chest compressions. Overall, data support that the prototype was user friendly, realistic and immersive. Conclusion and recommendations: Findings support that VR is a relatively novel, but interesting and enjoyable method by which to teach basic life support. Although it has wide-ranging potential, the specific purpose of the tool and the building of the VR context accordingly, does however, require some attention to optimise its effectiveness. User-friendliness, realism and interaction are important factors, which affect perceived levels of immersion and in the tested prototype, findings suggest some of these aspects require enhancement. Although high outlay costs are likely to reduce over time, ongoing resource implications alongside how to embed and sustain the current 'novelty' factor, also require consideration. References: Perkins G, Colquhoun M, Deakin C, et al . for the Resuscitation Council UK. Adult basic life support and automated external defibrillation 2015. Available online at: https://www.resus.org.uk/resuscitation-guidelines/adult-basic-life-support-and-automated-external-defibrillation/ Nolan J, Hazinski M, Aicken R, et al. Part I. Executive summary: 2015 international consensus on cardiopulmonary resuscitation and emergency cardiovascular care science with treatment recommendations. Resuscitation2015;95;e1–e32. Semeraroa F, Frisoli A, Bergamascob M, et al. Virtual reality enhanced mannequin (VREM) that is well received by resuscitation experts. Resuscitation2009;80:489–92. Semeraro F, Scapigliati A, Ristagno G, et al. Virtual reality for CPR training: How cool is that? Dedicated to the 'next generation'. Resuscitation2017;121:e1–e2.